Computation of displacements for nonlinear elastic beam models using monotone iterations - Philip Korman (International Journal of Mathematics and Mathematical Sciences)
We study displacement of a uniform elastic beam subject to various physically important boundary conditions. Using monotone methods, we discuss stability and instability of solutions. We present computations, which suggest efficiency of monotone methods for fourth order boundary value problems.